2015
DOI: 10.1016/j.jmbbm.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the residual thermal stresses on functionally gradated dental restorations

Abstract: The aim of this work was to study, using the finite element method (FEM), the distribution of thermal residual stresses arising in metal-ceramic dental restorations after cooling from the processing temperature. Three different interface configurations were studied: with conventional sharp transition; one with a 50% metal-50% ceramic interlayer; and one with a compositionally functionally gradated material (FGM) interlayer. The FE analysis was performed based on experimental data obtained from Dynamic Mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Similar finding was reported elsewhere [25,38]. This finding highlights the interface as a critical region in restorations and supports the evidences, reported elsewhere [11,43], of the interface as a crack nucleation and propagation site.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar finding was reported elsewhere [25,38]. This finding highlights the interface as a critical region in restorations and supports the evidences, reported elsewhere [11,43], of the interface as a crack nucleation and propagation site.…”
Section: Discussionsupporting
confidence: 93%
“…However, to the authors' best knowledge, no studies have explored the residual thermal stresses in graded ceramic restorations. Henriques et al [25,26] has addressed that topic in metal-ceramic restorations. Hence, the present study analyses the influence of the constructive design of a dental restoration as regard to the type of material and presence of an interlayer with varying composition (homogeneous and graded) and thickness, on the state of thermal residual stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These stresses were not incorporated in the model used in this study, although they would influence the results in a real experiment. Materials having gradation in composition (FGMs) are specially suited to cope with thermal stresses, promoting a reduction in stresses magnitude and smoothing their profiles [4,9,13,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that gradation of properties across the two materials present excellent results related to residual stresses for dental restorations [2026]. While several studies have demonstrated that graded prosthetic systems exhibit superior load-bearing capacity, improved damage resistance [23,24] and enhanced bond strength resistance [27], to the author’s best knowledge, little work has been reported on modeling thermal stresses in functionally graded restorations [22,25,28]. Functionally Graded Materials (FGMs) consist in a gradual change in the volume fraction between two phases [29].…”
Section: Introductionmentioning
confidence: 99%